RANDOMLY AMPLIFIED POLYMORPHIC DNA-FINGERPRINTING IDENTIFIES SUBGROUPS OF TRICHODERMA-VIRIDE AND OTHER TRICHODERMA SP CAPABLE OF CHESTNUT BLIGHT BIOCONTROL - ARISANATAC, I; HEIDENREICH, E; KUBICEK, CP (ELSEVIER SCIENCE BV, 1995)
Eleven strains of Trichoderma viride, 2 strains of the putative teleomorph Hypocrea rufa and 9 of several other Trichoderma sp. were characterized by random polymorphic DNA amplification (RAPD) fingerprinting and screened for their ability to antagonize growth of European strains of the chestnut blight causing fungus Cryphonectria parasitica, using a dual-culture assay. The best strains were found in the species T. harzianum, T. parceramosum, a distinguishable subgroup of T. viride and a not named Trichoderma sp. The successful application of these strains against chestnut blight in vivo is demonstrated.
Keywords: TRICHODERMA; CRYPHONECTRIA PARASITICA; CHESTNUT BLIGHT; BIOLOGICAL CONTROL; DNA POLYMORPHISM; RAPD-PCR; RAPD FINGERPRINTING; BIOLOGICAL-CONTROL; GENUS TRICHODERMA; REVISION; Microbiology